THE SPECIFICITY OF THE CONSTITUTIONAL COURT OF BOSNIA AND HERZEGOVINA WITH THE CRIMINAL RESPONSIBILITY FOR THE NON-EXECUTION OF ITS DECISIONS - Guska, Goran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Abstract: The Constitution of Bosnia and Herzegovina forms an integral part of the Dayton Peace Agreement, which created the present state of Bosnia and Herzegovina and it is specific in relation to the constitutions of most countries in the world. Thus, the Constitutional Court, which has the role of protector of the Constitution of Bosnia and Herzegovina, has its own specificities in relation to the Constitutional Courts of States which the Constitution protects in that way. One part of the paper is an analysis of the organization and jurisdiction of the Constitutional Court of Bosnia and Herzegovina with all its specificities as well as the decision of the court with the focus on those decisions related to the assessment of the constitutionality of norms of legislative acts in Bosnia and Herzegovina that are not in accordance with the Constitution of Bosnia and Herzegovina or mandatory international legal acts with a focus on their non-execution. The second part deals with criminal responsibility for non-execution of decisions of the Constitutional Court of Bosnia and Herzegovina as well as legal mechanisms in the function of securing the execution of decisions of the Constitutional Court. The answers to the questions when there is criminal responsibility for non- execution of the decisions of the Constitutional Court of Bosnia and Herzegovina, to which it specifically refers and in relation to such practical actions, we obtained by analyzing concrete decisions. Thus, we analyzed the decisions of the Constitutional Court regarding the Republic of Srpska Day and the referendum in Republic of Srpska in 2016.